2021
DOI: 10.3892/etm.2021.10455
|View full text |Cite
|
Sign up to set email alerts
|

mRNA expression level of CDH2, LEP, POSTN, TIMP1 and VEGFC modulates 5‑fluorouracil resistance in colon cancer cells

Abstract: Drug resistance severely affects the clinical efficacy of therapeutic agents in patients with colon cancer. The aim of the present study was to identify genes involved in drug resistance in colon cancer using bioinformatics analysis and to identify the underlying mechanisms in vitro. Genes associated with cancer recurrence and chemotherapy resistance were identified using data mining. Immunohistochemistry was performed to analyze the protein expression level of genes of interest in human colon cancer tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Interestingly, we found that CDH2 , a classical cadherin gene that has been previously implicated in cancer cell invasion and metastasis ( 55 , 56 ) to be downregulated in GC patients compared to normal controls. This finding is somewhat unexpected given the established role of CDH2 in promoting cancer cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, we found that CDH2 , a classical cadherin gene that has been previously implicated in cancer cell invasion and metastasis ( 55 , 56 ) to be downregulated in GC patients compared to normal controls. This finding is somewhat unexpected given the established role of CDH2 in promoting cancer cell invasion and metastasis.…”
Section: Discussionmentioning
confidence: 73%
“…Additionally, GSTM1 gene mutations are associated with colorectal cancer risk [19]. Leptin (LEP), the most famous adipokine highly expressed in colorectal cancer is related to the sensitivity of chemotherapy drug 5uorouracil (5-FU) [20,21]. Tissue metalloprotease inhibitor I (TIMP1) has been widely con rmed as a prognostic biomarker for colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is an important cancer treatment modality, and its effectiveness is challenging ( 75 ). Inherent or adventitious drug resistance to chemotherapy can result in poor treatment outcomes and tumor relapse, a major cause of treatment failure ( 76 ). The expression of ANXA1 plays a key role in chemotherapy resistance, and regulating ANXA1 expression represents a possible strategy for overcoming resistance.…”
Section: Anxa1mentioning
confidence: 99%